Development of Interactive Learning Media Using Lectora Inspire on Nervous System Topic for Senior High School Students - Muhamad Fahreza Imani; Ira Nurmawati (Indonesian Journal of Mathematics and Natural Science Education, 2022)
This study aims to describe the validity and response of students to interactive learning media on neural chapter. This media was developed by Lectora Inspire. This type of research was Research and Development (R&D) with a 4D model. Based on the results of media validation carried out by theory experts were 86% with a very valid category, then the results of validation by media experts obtained results of 89%, very valid category. And the results of validation by biology teachers were 96% with a very valid category. The results of the student response questionnaire showed a result of 87% with a very good category. Based on the results of the validation and student response questionnaires, it can be concluded that the learning media with the help of Lectora inspire on neural material is declared very valid and very good so that it can be used as a medium for learning biology for class XI SMA/MA students. Therefore, it can be assumed that lectora inspire-assisted learning media can be used in the biology learning process so that students can be more motivated in learning nervous system concepts.